Stimulation of adhesiveness, infectivity, and competitiveness for nodulation of Bradyrhizobium japonicum by its pretreatment with soybean seed lectin - Lodeiro, Aníbal Roberto (2000)
Soybean seed lectin stimulates adsorption of Bradyrhizobium japonicum to its host roots. Pretreatment of the rhizobia with soybean seed lectin for at least 6-12 h previous to their interaction with the plants was required to detect the stimulatory effect. This activity could be observed with as few as 1000 soybean seed lectin molecules per bacterium, and required specific carbohydrate binding. Infectivity and competitiveness for nodulation were also stimulated by preincubation of the rhizobia either with soybean seed meal extract or soybean seed lectin, the extract being more effective in enhancing competitiveness.